Mathematics Representation Ability Viewed from Adversity Quotient in SAVI Learning - Mahendra, Novira Rahmadian; Isnarto, Isnarto; Mulyono, Mulyono (Unnes Journal of Mathematics Education Research, 2020)
This research aims to describe mathematics representation ability of students seen from three categories of adversity quotient in Somatic, Auditory, Visualization, and Intellectual (SAVI) of eighth graders. This sequential explanatory typed mixed metod selected its subjects based on three categories of adversity quotient: quitter, camper, and climber. Technique of collecting data used mathematics representation ability test, adversity response profile questionnaire, and interview. The findings showed that the students taught by SAVI achieved actual minimum passing grade with descriptions of representation mathematics skill on visual representation, mathematical expression representation, and written text representation seen from quitter, camper, and climber during SAVI learning, resulted to various results for each category of AQ.